Regional variations in patient selection and procedural characteristics for cryoballoon ablation of atrial fibrillation. (3rd October 2022) - Scazzuso, F; Ptaszynski, P; Kaczmarek, K; Chun, K R J; Khelae, S K; Foldesi, C; Obidigbo, V; Kaplon, R; On, Y K; Al-Kandari, F; Okumura, K
Abstract: Background: Cryoballoon ablation is a well-established anatomical approach for pulmonary vein isolation (PVI) in patients with atrial fibrillation (AF). Although widely adopted, regional variations in standards of care have not been well characterized. Purpose: To evaluate regional variations in patient selection and procedural characteristics for PVI with cryoablation in the Cryo Global Registry (NCT02752737). Methods: Patients with AF were enrolled from May 2016 to October 2021 at 128 sites in 37 countries. Patients were treated with cryoballoon ablation according to local clinical practice. Baseline subject and procedural characteristics were summarized for 8 regions (Central Asia and Russia, East Asia, Europe, Middle East, North America, South Africa, South America, and Southeast Asia). Procedure-related serious adverse events (SAEs) were evaluated in a subset of patients with ≥7 days of follow-up. Results: A total of 3680 patients undergoing initial PVI for AF were included. Cryoballoon ablation was more commonly performed in patients with paroxysmal vs. persistent AF in all regions, and in males vs. females in all regions except Central Asia and Russia. Mean age ranged from 47±12 in the Middle East to 64±11 in East Asia. Regional variations were observed in the proportion of patients with common AF comorbidities undergoing cryoablation (Table 1). Median procedure time ranged from 61 (49–68) minutes in Central Asia and Russia to 95 (76–120) minutes in Southeast Asia. Median fluoroscopy time was ≤20 minutes in all regions. The use of 3D mapping was relatively uncommon except in North America (63.3%). Large variation was observed in the use of esophageal monitoring, whereas phrenic nerve monitoring was used in ≥97.7% of cases in all regions (Table 2). Same-day discharge was uncommon except in North and South America (37.8% and 26.5% of cases, respectively). Average freeze duration ranged from 153±41 seconds in Southeast Asia to 230±29 seconds in Central Asia and Russia. Mean number of applications per vein ranged from 1.2±0.4 in Central Asia and Russia to 2.1±1.0 in North America. Acute procedural success was ≥94.7% in all geographies and focal radiofrequency touch-up was required in ≤13.0% of cases. In 3126 subjects with ≥7 days of follow-up, 122 procedure-related SAEs were reported in 111 patients (3.6%), and 1 procedure-related death was reported during data collection. Conclusion(s): Despite regional variations in patient selection and procedural characteristics, PVI using cryoballoon ablation is performed with high acute success and short procedural times around the world. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Medtronic, Inc.